Ranking the Risk of Murabaha Sukuk base on the Financial Expert Opinions and a Comparison with Other Financial Instruments - Mohammad Naghi Nazarpour; Majid Habibian Naghibi; Hossein Kafshgar Jelodar (فصلنامه پژوهش‌های اقتصادی ایران, 2014)
Economic development in Islamic countries, emergence of new needs for financial resources and economic development, relative achievement in Islamic investment market, and the necessity of preventing riba have compelled Muslim scholars to design new Islamic financial instruments. Capabilities of Islamic contracts and the accumulation of experience in financial markets have made designing and administrating new Islamic financial instruments possible. Besides the necessity of designing new Islamic financial instruments and specialized jurisprudential investigation on sukuk to answer the increasing number of questions and meet the needs of investors, another issue should be also addressed, which is that of risk management. It must be considered in designing new Islamic financial instruments. The role of risk in this new financial instrument  should not be overlooked. That is, all the risks of the bonds should be identified and ranked. This paper is an attempt in ranking morabeheh sukuk risks using simple additive weighting (SAW) method and the technique for order preference by similarity to an ideal solution (TOPSIS).Using library resources, it was made possible to describe this instrument. Based on the risk rankings, inflation risk is the most important one among all primary and secondary market risks. Other risks, such as political, interest rates, and market risks as well as currency rate fluctuations are considered secondary. In other words, the risks of secondary market are more important, compared with those of the primary market. This paper investigated the validity of two hypotheses: (1) It is possible to rank the risks of morabehe sukuk, and (2) that bonds with fixed returns, such as murabaha are less risky, compared to the bonds with expected returns.